Respostas

A melhor resposta!
2014-05-24T00:04:01-03:00
E) 3x-11=x-11
3x-x=11-11
3x=0
x=3
f)x+7x-2x=96+2x
x+7x-2x-2x=96
4x=96
x=96/4
x=24
g)5x+2=11
5x=11-2
5x=9
x=9/5
h)4x-12=x
4x-x=12
3x=12
x=12/3
x=4
i)x+6=0,5
x=0,5-6
x=-5,5
j)8x-7=-2x+5
8x+2x=5+7
10x=12
x=12/10
x=6/5
3 5 3
vlw foi o mais rápido de todos para responder a pergunta! parabéns .:O
2014-05-24T00:05:54-03:00
E) 3x-11=x-11 => 3x - x = -11 + 11 => 2x = 0 => x = 0
.........
f)x+7x-2x=96+2x => x+7x-2x-2x=96 => 4x = 96 => x = 96/4 => x = 24
..........
g)5x+2=11 => 5x = 11 - 2 => 5x = 9 => x = 9/5 = 1,8
..........
h)4x-12=x => 4x - x = 12 => 3x = 12 => x = 12/3 = 4
..........
i)x+6=0,5 => x = 0,5-6 => x = -5,5
..........
j)8x-7=-2x+5 => 8x + 2x = 5 + 7 => 10x = 12 => x = 12/10 = 1,2
2 5 2